PREOPERATIVE PREDICTORS FOR SUCCESSFUL COMPLETION OF LAPAROSCOPIC CHOLECYSTECTOMY (Indian Journal of Applied-Basic Medical Sciences, 2020)
BACKGROUND: laparoscopic cholecystectomy is one of the most commonly performed laparoscopic procedure in the world and it is the gold standard for the treatment of various gallstone disease. METHOD: The proposed prospective study was conducted in Smt. N.H.L. Municipal Medical College. A total 100 patients of symptomatic gall stone disease of all age groups both males and females were included in this study. RESULTS: Male sex, Positive Murphy’s sign, acute cholecystitis, leukocytosis, Pericholecystic fluid collection and edematous GB wall in ultrasonography is associated with significantly higher risk of conversion of laparoscopic cholecystectomy. CONCLUSIONS: Various clinical, hematological and radiological predictions done preoperatively may help the patient as well as the surgeon in being better prepared for the intraoperative risk of conversion to open procedure and postoperative complications.
Keywords: PREDICTORS; LAPAROSCOPIC CHOLECYSTECTOMY; outcome